Exploring the Relative Economics of Tobacco and its Major Competing Crops – A Study in the Terai Region of West Bengal - Kar, Shouvik; Das, Soumyadeep; Ashad, Rahul; Das, Kalyan Kanti (International Journal of Bio-resource and Stress Management, 2026)
This present study was conducted during the months of January–August, 2023 under the Department of Agricultural Economics, Uttar Banga Krishi Viswavidyalaya, Pundibari, Cooch Behar, India to explore the reasons behind the persistence and rising trend of tobacco cultivation despite the implementation of multiple tobacco control laws in India. By adopting the technique of multi-stage random sampling, the researchers drew 72 samples of farmer respondents in the Cooch Behar district of West Bengal. The study aimed to elucidate a clue to the core question, ‘why did farmers persist in cultivating tobacco despite the enactment of tobacco-related laws and awareness campaigns of its harmful effects?’ Standard statistical/economic tools and concepts were used to address the study’s diverse objectives. Maize and potato were found to be the two most prominent competing crops of tobacco during the rabi season. Our study proved the superiority of the two most popular cultivars of tobacco, i.e., Jati and Motihari, over the competing crops in terms of cost of cultivation, net return, cost of production, etc. Return per rupee (in terms of Cost A1) happens to be 4.76 and 4.70 for Jati and Motihari tobacco, which is substantially higher than that of maize (2.56) and potato (2.70). The study’s outcome indicated that farmers prefer tobacco cultivation due to its greater profitability, established market demand for tobacco products, simplicity and ease of cultivation, and other favorable factors. Also, compared to other crops, tobacco growers experienced fewer instances of market malfunction in the study area.